Plant communities with Helianthus tuberosus L. in the towns of the Upper Silesian Industrial Region (southern Poland) - Kompała-Bąba, Agnieszka; Błońska, Agnieszka (Biodiversity: Research and Conservation, 2008)
The aims of the research were: to show the floristic composition of patches with participation of Helianthus tuberosus, to find the major environmental gradients in species composition of these patches and to compare plant communities with this species from Poland with those recorded in neighbouring European countries. Fifty four phytosociological relevés, made in a variety of ruderal habitats in the towns of the Upper Silesian Industrial Region (Poland), were analysed using the Correspondence Analysis (CA). To identify the main environmental gradients in the floristic composition of relevés the CA site scores were correlated, using the Kendall correlation coefficient, with the following explanatory variables: Shannon H’ index of species diversity, the number of species from the Convolvuletalia sepium order, the Calystegion sepium alliance, the Onopordetalia acanthii order, the Molinio-Arrhenatheretea class, the Stellarietea mediae class; mean Ellenberg indicator values for light, moisture, temperature, soil reaction and nitrogen. Two major gradients in species data were detected: (i) from plant communities of abandoned meadows of the Molinio-Arrhenatheretea class to nitrophilous communities of the Convolvuletalia sepium order and (ii) a gradient related to the number of species of the Stellarietea mediae class and to the indicator value for light. Helianthus tuberosus stands recorded in European countries can be divided into two separate groups. The first group is differentiated by species of the Onopordetalia acanthii order and higher participation of meadow species from the Molinio-Arrhenatheretea and Stellarietea mediae classes. The second group is characterized by a high frequency of nitrophilous species from the Convolvuletalia sepium order.